2017
DOI: 10.1108/jefas-02-2017-0034
|View full text |Cite
|
Sign up to set email alerts
|

The short-term response of the Hispanic noncitizen population to anti-illegal immigration legislation

Abstract: Purpose This paper aims to examine the short-term effect of the Arizona Immigration Law of 2010 (SB 1070) on the noncitizen Hispanic state population. Design/methodology/approach To get a consistent estimate of this effect, a synthetic control method has been used to calculate a suitable counterfactual. Findings Results indicate that this bill produced a statistically significant short-term reduction in the proportion of noncitizen Hispanics in Arizona between 10 and 15 per cent. However, the evidence sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 19 publications
0
7
0
1
Order By: Relevance
“…There is some evidence that restrictive state and local immigration laws lead to outmigration of immigrants and/or Latinos from the state (Bohn et al, 2014; Capps et al, 2011; Ellis et al, 2014; Orrenius and Zavodny, 2017; Watson, 2013; Wills and Commins, 2018). However, effects may be temporary (Sánchez, 2017), not all studies find significant outmigration in all states with restrictive laws (García, 2013; Orrenius and Zavodny, 2017), and there are conflicting findings about whether it is more-advantaged or less-advantaged Latinos who leave (Bohn et al, 2014; Ellis et al, 2014; Watson, 2014). Alternately, these families may have remained in the state but declined to participate in NHIS.…”
Section: Discussionmentioning
confidence: 99%
“…There is some evidence that restrictive state and local immigration laws lead to outmigration of immigrants and/or Latinos from the state (Bohn et al, 2014; Capps et al, 2011; Ellis et al, 2014; Orrenius and Zavodny, 2017; Watson, 2013; Wills and Commins, 2018). However, effects may be temporary (Sánchez, 2017), not all studies find significant outmigration in all states with restrictive laws (García, 2013; Orrenius and Zavodny, 2017), and there are conflicting findings about whether it is more-advantaged or less-advantaged Latinos who leave (Bohn et al, 2014; Ellis et al, 2014; Watson, 2014). Alternately, these families may have remained in the state but declined to participate in NHIS.…”
Section: Discussionmentioning
confidence: 99%
“…These controls, as seen in Table 1, are the percentage of a state's population in a given year that is Hispanic or foreign-born, drawn from the American Community Survey 1-Year Estimates 2003-2016 from Social Explorer (Ruggles et al, 2017; U.S. Census Bureau, 2017). If, for example, as some studies have suggested (Amuedo-Dorantes and Lozano, 2015; Bohn, Lofstrom, and Raphael, 2014;Hoekstra and Orozco-Aleman, 2014;Sánchez, 2017), migration patterns may have altered in Arizona following the passage of the Legal Arizona Worker's Act in 2007 or SB 1070 in 2010, we might expect that those remaining in Arizona could be less impacted socially compared to how those who left would have been. In other words, controlling for changes in these populations over time can help to determine if these changes are important in understanding the results presented below.…”
Section: Key Predictors and Controlsmentioning
confidence: 98%
“…En el contexto de este documento, es decir, un estudio comparativo en el cual se posee una muestra pequeña con intervenciones a nivel agregado (países y estados), es una complicación fundamental encontrar controles adecuados que no hayan sido afectados por la intervención y que posean características similares a las de la unidad intervenida (Abadie et al, 2010;Collier, 1993;Lijphart, 1971;Sánchez, 2017).…”
Section: Modelamiento Econométricounclassified